Pengaruh Motivasi, Prestasi dan Pengembangan Karir terhadap Kepuasan Kerja Karyawan pada PT. Kajima Kabupaten Pekalongan - Maulana, Faiz Takhta; Fauzan, Mohammad (IPM2KPE, 2024)
The objectives of this study are (1) Analyze and explain the effect of work motivation on employee job satisfaction, (2) Analyze and explain the effect of job performance on employee job satisfaction, and (3) Analyze and explain the effect of career development on employee job satisfaction at PT. Kajima Pekalongan. This research is a type of explanatory research, which is testing hypotheses and explaining the influence between variables from hypotheses that have been formulated The number of research samples was 100 employees. The research data was obtained through the distribution of questionnaires through googleform links to employees of PT. Kajima Pekalongan. Furthermore, the data is processed using SPSS 25. For the purposes of data analysis, instrument tests are carried out by conducting validity tests and reliability tests; Test the model through Test F, and Test determination (R²) and then Test Hypothesis (Test t). Research findings: [1] Work motivation has a positive effect on job satisfaction. [2] Job performance has no effect on job satisfaction. [3] Career development positively affects job satisfaction. Based on research findings that the variables of work motivation and career development have a positive effect on job satisfaction. This gives a strong signal to the Chairman of PT. Kajima Pekalongan Regency that in recruiting prospective employees, it is necessary to consider the ownership of psychological/mental values of prospective employees, there must be similarities with the value of share values or core values of the company. Keywords: Work Motivation, Career Development, Employee Job Satisfaction